Analysis of Genetic Structuralism in the Novel Egosentris by Syahid Muhammad - Farah Nazifa; Lina Sundana (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze genetic structuralism in the novel Egosentris by Syahid Muhammad by focusing on structural elements, human facts, and the author’s worldview. The research employs a descriptive qualitative method, with the novel Egosentris serving as the primary data source. The research population consists of the entire content of the novel, while the sample comprises selected textual excerpts relevant to the genetic structuralism approach. The data are in the form of quotations that represent structural elements, human facts, and the author’s worldview, which were collected through intensive reading and systematic note-taking techniques. The researcher acts as the main research instrument, supported by data classification tables. The collected data were analyzed using descriptive qualitative analysis by relating the structure of the literary work to its social context, the author’s background, and the worldview underlying the creation of the novel. The results indicate that 67 relevant excerpts were identified, consisting of 60 excerpts related to structural elements such as theme, plot, characters and characterization, setting, point of view, and moral values that dominate the narrative development, 3 excerpts reflecting human facts in the form of psychological conflicts, social relations, and social pressures experienced by the characters, and 4 excerpts representing the author’s worldview that convey criticism of egocentric attitudes, a lack of empathy, and the search for personal identity in social life. These findings confirm that the novel Egosentris demonstrates a close relationship between literary structure and the author’s social reality as examined through the genetic structuralism approach.